Analysis On Students’ Scientific Literacy of Newton’s Law and Motion System in Living Things - Indah Slamet Budiarti*; Tanta Tanta (Jurnal Pendidikan Sains Indonesia, 2021)
The 21st century skills focus on scientific literacy competences in various urban and rural areas, one of which is Papua. Scientific literacy has competences to identifying scientific problems, explaining scientific phenomena, and utilizing scientific findings to solve problems. The purpose of this study was to determine the science literacy competences of IPA class VIII students of SMPN 5 Jayapura. Scientific literacy is competencies to understanding science, communicating science, and applying scientific conceptual to solve problems. A descriptive qualitative approach is used as this type of research. This research was conducted at SMPN 5 Jayapura. The sample selection used purposive sampling technique. There were 33 students who became respondents and teste in this study. The research instruments were documentation, observation, tests and interviews. The average percentage of competency aspects with indicators of identifying scientific problems, explaining scientific phenomena, and utilizing scientific findings is below 80%. The average percentage of aspects of knowledge about the concept of motion, with sub-concepts of regular motion, force, and Newton's laws is below 90%. The average percentage of human, animal and plant movement systems is below 70%. The highest score, average, median, mode, and lowest score of the cognitive scores of students' scientific literacy abilities were 100; 68.33; 75; 80; and 30. The scientific literacy competences of grade 8 students of SMPN 5 Jayapura are still low, which is shown in terms of the percentage of competence and is classified as moderate for the knowledge aspect. The conclusion of this study is that the scientific literacy competences of students at SMPN 5 Jayapura are in the sufficient category.